Small Specimen Test Techniques: Fourth Volume 2002
DOI: 10.1520/stp10817s
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Simulations and Empirical Correlation for Charpy-V and Subsize Charpy Tests on an Unirradiated Low-Alloy RPV Ferritic Steel

Abstract: Charpy-V test results are widely used for the surveillance program of RPV (Reactor Pressure Vessel) embrittlement by neutron irradiation. Service life extension of nuclear power plants and more stringent safety requirements are increasing the request for small test specimens such as subsize Charpy. Furthermore, the empirical correlation formulas between conventional Charpy-V and fracture toughness are often questionable. Therefore, prior to use of reduced size specimens, different hypotheses have to be validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The present study uses a modified version of the model [22]. Another solution was proposed by Sainte-Catherine et al [58].…”
Section: Discussion: Simulating the Charpy Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study uses a modified version of the model [22]. Another solution was proposed by Sainte-Catherine et al [58].…”
Section: Discussion: Simulating the Charpy Testmentioning
confidence: 99%
“…Such comparisons were carried out by other authors for steels similar to the material investigated in the present study [10][11][12][13]. Simulations of sub-size Charpy specimens were also proposed in [14] The material used in the present study is fully described in a companion paper [1]. This steel (A508 Cl.3) is used to manufacture the pressure vessel of French nuclear pressurized water reactors.…”
mentioning
confidence: 99%
“…There are limited studies that focus on brittle fracture of CVN impact tests at low temperatures. For instance Catherine et al 13 have developed the Beremin (1983) cleavage model to simulate CVN and sub-size CVN impact tests at low temperature (À90 C). From their study they found that the results showed a good transferability potential.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited studies that focus on brittle fracture of the DWTT or Charpy V-Notch (CVN) impact tests at low temperatures. For instance Sainte Catherine et al [5] have developed the Beremin (1983) cleavage model to simulate CVN and Sub-Size CVN impact tests at low temperature (-90°C). From their study they found that the results showed a good transferability potential.…”
Section: Introductionmentioning
confidence: 99%